2017
DOI: 10.1097/md.0000000000006788
|View full text |Cite
|
Sign up to set email alerts
|

Widely differing screening and treatment practice for osteoporosis in patients with inflammatory bowel diseases in the Swiss IBD cohort study

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 52 publications
1
27
0
1
Order By: Relevance
“…Given this risk profile in addition to age-related bone loss, Dual Energy X-ray Absorptiometry (DXA)-screening among senior IBD patients with steroid exposure and/or additional risk factors is recommended [52,86]. However, recent data indicate an inconsistent implementation of osteoporosis screening and treatment even in countries with a developed health-care system [87].…”
Section: Healthcare Maintenancementioning
confidence: 99%
“…Given this risk profile in addition to age-related bone loss, Dual Energy X-ray Absorptiometry (DXA)-screening among senior IBD patients with steroid exposure and/or additional risk factors is recommended [52,86]. However, recent data indicate an inconsistent implementation of osteoporosis screening and treatment even in countries with a developed health-care system [87].…”
Section: Healthcare Maintenancementioning
confidence: 99%
“…Regarding the screening and treatment of osteoporosis in adult patients with IBD, a Swiss IBD cohort study of 877 patients reported that 253 of the 877 participants underwent dual-energy X-ray absorptiometry (DXA), which revealed osteoporosis in about 20% of the tested patients. 10) In practice, treatment rates for IBD patients with osteoporosis were suboptimal; success rates of only 55% for calcium and 65% for vitamin D were noted, 10) remaining low at 53% for calcium and 58% for vitamin D even in patients also on systemic steroid therapy. 10) Only 29% of IBD patients with osteoporosis in that study were treated with bisphosphonate.…”
Section: Screening and Treatment Practice For Bone Health In Ibdmentioning
confidence: 99%
“…10) In practice, treatment rates for IBD patients with osteoporosis were suboptimal; success rates of only 55% for calcium and 65% for vitamin D were noted, 10) remaining low at 53% for calcium and 58% for vitamin D even in patients also on systemic steroid therapy. 10) Only 29% of IBD patients with osteoporosis in that study were treated with bisphosphonate. Overall, the screening and treatment of osteoporosis were not timely in IBD patients, although appropriate calcium and vitamin D supplementation was significantly associated with improvement of BMD over time.…”
Section: Screening and Treatment Practice For Bone Health In Ibdmentioning
confidence: 99%
See 2 more Smart Citations